The Association of Prepregnancy Body Mass Index with Pregnancy Outcomes in Chinese Women - Jing Zhang; Wensheng An; Li Lin (Journal of Diabetes Research)
Our study was to evaluate the association between prepregnancy body mass index (BMI) and pregnancy outcomes. A total of 1546 women who attended prenatal care clinics and delivered at the Peking University International Hospital, Beijing, China, from October 2018 to April 2020 was included. This research explored gestational, perinatal, and postpartum outcomes, including gestational diabetes, anemia, preeclampsia, preterm premature rupture of membranes (PPROM), and postpartum hemorrhage. Participants were divided into underweight (BMI<18.5 kg/m2), normal weight (18.5 kg/m2≤BMI≤23.9 kg/m2), overweight (24 kg/m2≤BMI≤27.9 kg/m2), and obese (BMI≥28 kg/m2) groups. Logistic regression analysis was used to analyze the association between prepregnancy BMI and pregnancy outcomes, and odds ratio (OR) with 95% confidence interval (95% CI) was calculated. After adjusting potential confounders, the risk of PPROM was higher in the underweight group than the normal weight group (OR=1.864, 95% CI: 1.269-2.737, P<0.01). Prepregnancy obesity was associated with higher odds of gestational diabetes (OR=2.649, 95% CI: 1.701-4.126, P<0.001) and preeclampsia (OR=3.654, 95% CI: 1.420-9.404, P<0.01) than the normal weight group, whereas it correlated with the lower risk of anemia (OR=0.300, 95% CI: 0.128-0.704, P<0.01). Our findings may provide evidence for the importance of keeping normal weight for Chinese women when preparing for pregnancy.